Estimation of the Petrophysical Properties of the Lower Cretaceous Yamama (YC) Formation in Siba Field - Hadi, Zainab A.; Al-Fatlawi, Omar F.; Kadkhodaie, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
In southern Iraq, the Yamama Formation has been a primary carbonate resource since the Lower Cretaceous era. This study covers Siba Field, which is located in southeastern Iraq. This paper will be devoted to a YC unit of study. The most crucial step in reservoir management is petrophysical characterization. The primary goal of this research is to assess the reservoir features and lithology of the Yamama (YC) Formation in the Siba region. Accessible excellent logs include sonic, density, neutron, gamma-ray, SP, and resistivity readings. The Interactive Petrophysics (IP4.4) program examined and estimated petrophysical features such as clay volume, porosity, and water saturation. The optimum approach was the neutron density and clay volume calculation using the Gamma Ray Method (VclGR), it was 0.246 in SB-6 since they are not impacted by anything. The Archie method was chosen due to its suitability for limestone. The lithology and mineralogy of the formations were determined using M-N cross plots; the diagram revealed that the Formation was composed of limestone. The Archie parameter was determined using the Pickett plot and formation water resistivity from the Pickett plot and SP log where the results were similar in all wells (RW=0.016, m=2.08, n=2.3, a=1.1). In addition, the higher section of the formation has good reservoir qualities such as density is (2.368g/cc), porosity is (PHIE=0.117) in SB-6.